Anti-fungal bandages containing cinnamon extract - GÜNDÜZ, OĞUZHAN (WILEY, 2019)
Cinnamon-containing polycaprolactone (PCL) bandages were produced by pressurised gyration and their anti-fungal activities against Candida albicans were investigated. It was found that by preparing and spinning polymer solutions of cinnamon with PCL, fibres capable of inhibiting fungal growth could be produced, as observed in disk diffusion tests for anti-fungal susceptibility. Fascinatingly, compared with raw cinnamon powder, the novel cinnamon-loaded fibres had outstanding long-term activity. The results presented here are very promising and may indeed accelerate a new era of using completely natural materials in biomedical applications, especially in wound healing.
Keywords: anti-fungal; bandages; Cinnamon; healthcare; mass production; ESSENTIAL OILS; CINNAMALDEHYDE; CARVACROL; THYMOL